Quality of Population Administration Services at the Office of the Population and Civil Registry Service in Jayapura City - Dorthea Renyaan; Ilham (Jurnal Multidisiplin Madani, 2023)
This study aims to determine the quality of population administration services at the Jayapura City Population and Civil Registry Service. The method used is a type of qualitative research. Data obtained from observations, interviews, documentation, and literature studies. Data analysis was carried out in the stages of presenting data, data reduction and drawing conclusions. The results of this study indicate that the quality of population administration services can be assessed from five dimensions, namely: Tangible aspect, service support facilities are adequate and satisfy the community. Aspects of Reliability, the service has been carried out properly. This is marked by the fast time for processing/making service products according to the time in the SOP, and there are no fees charged by the public or free of charge. In the responsiveness aspect, employees serve the community well by responding to questions asked by the community and providing direction and serving in a friendly and courteous manner. Assurance aspect, the Jayapura City Population and Civil Registry Service has provided guarantees for ease of service and security guarantees for people who apply for services. In the aspect of empathy, the Jayapura City Population and Civil Registry Office has provided good and satisfying service. This is achieved because the serving staff have a friendly attitude in dealing with requests, criticisms, and suggestions given by the public. As a recommendation, the Jayapura City Population and Civil Registry Service should add service support facilities or service infrastructure facilities such as the provision of generator engines to anticipate when there is a blackout. Meanwhile, to overcome the problem of frequent offline network interruptions, it is best to try by sending a letter to the head office. Promoting the official web page of the Jayapura City Population and Civil Registry Service to the public, for example by conducting socialization of web services to each district and village/urban village